Inflammatory repercussions in female steroid responsive glands after perinatal exposure to bisphenol A and 17-β estradiol - Leonel, Ellen Cristina Rivas [UNESP]; Ruiz, Thalles Fernando Rocha [UNESP]; Bedolo, Carolina Marques [UNESP]; Campos, Silvana Gisele Pegorin [UNESP]; Taboga, Sebastião Roberto [UNESP] (Wiley, 2021)
The mammary gland (MG) and female prostate are plastic reproductive organs which are highly responsive to hormones. Thus, endocrine disruptors, such as bisphenol A (BPA) and exogenous estrogens, negatively affect glandular homeostasis. In addition to previously described alterations, changes in inflammatory markers expression also trigger the development of a microenvironment that contributes to tumor progression. The current work aimed to evaluate the inflammatory responses of the MG and prostate gland to BPA (50 µg/kg) and 17-β estradiol (35 µg/kg) exposure during the perinatal window of susceptibility. The results showed that at 6 months of age there was an increase in the number of phospho-STAT3 (P-STAT3) positive cells in the female prostate from animals perinatally exposed to 50 µg/kg BPA daily. In addition, the number of macrophages increased in these animals in comparison with nonexposed animals, as shown by the F4/80 marker. Despite an increase in the incidence of lobuloalveolar and intraductal hyperplasia, the MG did not show any difference in the expression of the four inflammatory markers evaluated: tumor necrosis factor-α, COX-2, P-STAT3, and F4/80. Analysis of both glands from the same animal led to the conclusion that exposure to endocrine disruptors during the perinatal window of susceptibility leads to different inflammatory responses in different reproductive organs. As the prostate is more susceptible to these inflammatory mechanisms, it is reasonable to affirm that possible neoplastic alterations in this organ are related to changes in the inflammatory pattern of the stroma, a characteristic that is not evident in the MG.
Keywords: endocrine disruptor; female prostate; inflammation; mammary gland; morphology